Commodification of religion and islamic cultural industry through social media - Khadijah, Siti (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: WEF (World Economic Forum) data in 2022 shows an increase in the number of hijab users in Indonesia by 5.7%. It seems that easily accessible social media is one of the factors influencing the growth of the fashion industry. because anyone can see, create and even spread ideas, concepts and works with various purposes. Methods: This study employs a qualitative approach with content analysis of social media platforms, interviews with Muslim celebrities, and literature reviews on the commodification of religion and fashion trends. Data collection focuses on identifying the motives behind hijab fashion promotion and its impact on public perception. Findings: The Islamic cultural industry creates opportunities for the commodification of religion, particularly through the fashion industry in Indonesia. Muslim celebrities use social media to influence hijab fashion trends, which carry both positive and negative meanings. Social media serves as a platform for interaction, inspiration, and sharing experiences, making hijab fashion more modern and increasingly secular. Conclusions: The study finds that social media plays a crucial role in shaping hijab fashion trends in Indonesia, driven by the dual motives of Muslim celebrities—ranging from attraction and inspiration to existential expression. This phenomenon reflects the commodification of religion, where hijab fashion is increasingly modernized and secularized, blurring traditional religious boundaries and reinforcing consumer-driven identities. Novelty/Originality of This Study: The novelty of this study lies in its exploration of the dual motives of Muslim celebrities in shaping hijab fashion trends through social media, highlighting the commodification of religion and the evolving modern-secular interpretation of hijab.